Effect of probiotics during vonoprazan‐containing triple therapy on gut microbiota in Helicobacter pylori infection: A randomized controlled trial. Issue 3 (24th March 2020) - Kakiuchi, Toshihiko; Mizoe, Akihiko; Yamamoto, Kentaroh; Imamura, Ichiro; Hashiguchi, Kazutoshi; Kawakubo, Hiroharu; Yamaguchi, Daisuke; Fujioka, Yasuhiko; Nakayama, Aiko; Okuda, Masumi; Matsuo, Muneaki
Abstract: Background: Probiotics are beneficial to patients with Helicobacter pylori infections by modulating the gut microbiota. Biofermin‐R (BFR) is a multiple antibiotic‐resistant lactic acid bacteria preparation of Enterococcus faecium 129 BIO 3B‐R and is effective in normalizing the gut microbiota when used in combination with antibiotics. This study aimed to determine the effect of BFR in combination with vonoprazan (VPZ)‐based therapy on gut microbiota. Methods: Patients with positive urinary anti‐ H pylori antibody test (primary test) and fecal H pylori antigen test (secondary test) were examined. Patients in group 1 (BFR − ) received VPZ (20 mg twice daily), amoxicillin (750 mg twice daily), and clarithromycin (400 mg twice daily) for 7 days. Patients in group 2 (BFR + ) received BFR (3 tablets/day) for 7 days, in addition to the aforementioned treatments. Following treatment, the relative abundance, α‐diversity, and β‐diversity of gut microbiota were assessed. Results: Supplementation with BFR prevented the decrease in a‐diversity after eradication therapy (Day 7). β‐diversity was similar between groups. The incidence rate of diarrhea was non‐significantly higher in the BFR − than in the BFR + group (73.1% vs 56.5%; P  = .361). Stool consistency was comparable in the BFR + group on Days 7 and 1 (3.86 ± 0.95 vs 3.86 ± 1.46; P  = .415). Conclusion: Biofermin‐R combined with VPZ‐based therapy resulted in higher microbial α‐strain diversity and suppressed stool softening during H pylori eradication therapy.